2005
DOI: 10.1007/s00436-004-1292-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of duration of immunity in crossbred cattle immunized with glycoproteins isolated from Hyalomma anatolicum anatolicum and Boophilus microplus

Abstract: To develop immunoprophylactic measures against multi-tick infestation, two glycoproteins of 34 and 29 kDa were isolated from the larvae of Hyalomma anatolicum anatolicum and Boophilus microplus, respectively, and assessed for their efficacy against experimental challenge infestations. The synergistic effect of the antigens in the presence of incomplete Freund's adjuvant was found to confer protection (DT%) in animals against 56.48% of larvae and 52% of adults of H. a. anatolicum, while the effect was 40% again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Thus, population-limiting property of any plant extract need to be evaluated to assess the efficacy of extracts. In the present study, the effects of A. squamosa seed extract on the future progeny of the exposed ticks were evaluated by estimating the reproductive index (Ghosh et al 2005), and the data revealed a significant (P<0.05) reduction in the egg-laying capacity of all the ticks exposed to different concentrations (3-8% concentration) of A. squamosa in comparison to the ticks of control group. Previously, Srivastava et al (2008) assessed the population-limiting potential of neem seed extract, and a significant reduction of 0.34% in the RI of the ticks treated with 8% concentration of the extract in comparison to the ticks of control group was recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, population-limiting property of any plant extract need to be evaluated to assess the efficacy of extracts. In the present study, the effects of A. squamosa seed extract on the future progeny of the exposed ticks were evaluated by estimating the reproductive index (Ghosh et al 2005), and the data revealed a significant (P<0.05) reduction in the egg-laying capacity of all the ticks exposed to different concentrations (3-8% concentration) of A. squamosa in comparison to the ticks of control group. Previously, Srivastava et al (2008) assessed the population-limiting potential of neem seed extract, and a significant reduction of 0.34% in the RI of the ticks treated with 8% concentration of the extract in comparison to the ticks of control group was recorded.…”
Section: Discussionmentioning
confidence: 99%
“…The live ticks from all the animals were weighed individually and kept in tick rearing tube for oviposition. The RI, alteration in the egg mass production (DO%), alteration in the weight of adult tick (DR%), and the percentage efficacy of the extract (E%) (Ghosh et al 2005) of ticks from all the groups of animals were calculated as follows:…”
Section: In Vivo Studymentioning
confidence: 99%
“…(B.) microplus were collected by checking the ear bag daily and the efficacy of vaccine formulations was evaluated (Ghosh et al 2005).…”
Section: Cattle Immunizations and Tick Infestationsmentioning
confidence: 99%
“…The application was done by cotton swab. The tick feeding bags were checked daily, and entomological data on mortality percentage, alteration in the egg mass production (DO%), alteration in the weight of adult ticks (DR%), and percentage efficacy of the extract (E%) were calculated as follows (Ghosh et al 2005 …”
Section: In Vivo Trialmentioning
confidence: 99%